Early Childhood Football Achievement Development System at the AFQOZ Grobog Club, Tegal Regency - Adi Pratama, Okky Rizki; Sugiharto, Sugiharto; Nasuka, Nasuka (Journal of Physical Education and Sports, 2021)
Researchers found several problems from the inadequate early age coaching of the AFQOZ Club in Tegal Regency. The research aims to determine 1)Fostering early childhood football achievements, 2)Training program, 3)Funding sources, 4) facilities and infrastructure, 5)The role of the community athletes, 6)The role of the coach. Qualitative research by describing and analyzing, the target of research on fostering the early childhood achievement of the AFQOZ Club. The location of this research is in the AFQOZ Club, Pangkah District, Tegal Regency. Collecting data using observation techniques, interviews, documentation. The research results are as follows: 1)Fostering the early childhood football achievements of the AFQOZ Club is quite good, because it often uses simulations and there is a tiered system in each age group up to the Elite Pro Academy, 2)The training program is good because it refers to PSSI standards according to the age group in the Club, 3)The club's source of funds comes from the AFQOZ Collection, which can be said to be good, even though the salary of the coach and manager is small, but the facilities obtained are quite adequate, such as club transportation,4)The facilities and infrastructure are quite a lot of good quality and modified, 5)Community support is lacking for the club, the local government does not release field management to the club to interfere with the training program, 6)The trainer becomes a motivator and initiator, plays a good role because it can bring fostered athletes have made achievements in football events.